Mutual-to-stock conversions and depositor welfare: Evidence from U.S. savings banks - Girotti, Mattia; Meade, Richard (Journal of Financial Intermediation, 2026)
We empirically study how banks’ conversions from mutual to stock ownership affect depositor welfare. Using U.S. data and a discrete choice model of deposit account demand, we show that when a bank is mutual, depositors are less sensitive to price, and each unit of cash and liquidity services is valued more positively. We then examine how mutual-to-stock conversions affect deposit account characteristics and combine these changes with our demand estimates to assess conversions’ impact on depositor welfare. Our estimates indicate that conversions increase depositor welfare, challenging the premise that mutual banks operate for the benefit of their members.